POTENSI IKAN KAKAP PUTIH (Lates calcarifer Bloch, 1790) DI SUNGAI KUMBE DISTRIK MALIND KABUPATEN MERAUKE - Mohamad Hari Widodo; Edy HP. Melmambessy; Siti Masiyah (Universitas Musamus, Merauke, Papua, 2016)
Research objectives is to examine the potential white snapper (Lates calcarifer, Bloch , 1790 ) in a kumbe river malind district kabupaten merauke .Of research in the kumbe river malind district , start october 2014 up to january 2015. A method of the sample collection done by using the method purposive random sampling, namely the sample adapted to the purposes research. Data analysis includes: catch per unit effort (CPUE), maximum sustainable yield (MSY) and efforts sustainable (Fopt). The results of the study: value CPUE for a unit arrestgill nets fixed (set gill net during the month of oktober-januari the lowest in november at station 1 with value CPUE 0.4285 kg/unit, while value CPUE for a unit arrest is highest in station III in october with the cpue 5.2272 kg/unit .The maximum sustainable yield (MSY) based on model fox in the Kumbe River District Malind of 212,763 kg, Fopt = 33,783 hauling. Potential white snapper on the Kumbe River is still quite good and fishing white snapper should be encouraged, however it is important to ensure that does not exceed MSY value.